The Mythology of South America - Bierhorst, John. (New York : William Morrow, 1988)
Discusses the mythology from Indians of various regions of South America, describing origins, comparing the similar tales, and presenting some of the myths themselves
Includes index
Bibliography: p. 255-263
Keywords: Indians of South America -- Religion; Indian mythology -- South America